Mycelial compatibility, anastomosis, and nucleus numbers of eight Mexican Hirsutella citriformis strains isolated from Diaphorina citri - Pérez-González, Orquídea; Gomez-Flores, Ricardo; Tamez-Guerra, Patricia (PeerJ, 2021)
Background Among entomopathogenic fungi, H. citriformis has been recognized as potential biocontrol agent against the Asian citrus psyllid Diaphorina citri (Hemiptera: Liviidae). Nevertheless, this fungus is poorly characterized. Previous molecular studies have shown high sequence similarities among strains, but significant differences in Diaphorina citri virulence. Objective The aim of the present study was to determine mycelial compatibility and anastomosis, and nucleus numbers in mycelium and conidia of eight H. citriformis strains isolated from mycosed D. citri adults collected from several Mexican states. Methods Mycelial compatibility and anastomosis evaluation was performed after pairing strains, leading to 36 confrontations, and cultured in chlorate minimum medium to obtain mutants for vegetative compatibility group. Results Hypha or conidia nuclei were visualized with safranin-O and 3% KOH, and 0.05% trypan blue–lactophenol solution. H. citriformis strains showed compatibly and anastomosis events after confrontation. In addition, they showed one nucleus per conidium and mycelium section. It was not possible to obtain H. citriformis nit mutants from the chlorate concentrations tested. Conclusions To date, this is the first report demonstrating mycelial compatibility, anastomosis occurrence, and hyphae and conidia nuclei number among H. citriformis strains.
Keywords: Nit mutants; Nuclei; Fungus mexican native strains; Mycelial characterization